Geographic expansion of artemisinin resistance - Müller, Olaf; Lu, Guangyu; Seidlein, Lorenz von (Journal of travel medicine, 2019)
Background Artemisinin-based combination therapy (ACT) is the global standard of care for uncomplicated falciparum malaria. First reports of ACT resistance came from western Cambodia and the Thailand-Cambodia border in 2002-2004. The subsequent emergence and expansion of Plasmodium falciparum strains resistant to the artemisinin component and ACT are now threatening the efficacy of falciparum malaria treatment. Methods We performed a literature review on the history and the current degree of geographic expansion of artemisinin and ACT resistance. Resistance against artemisinins is defined as >5% of patients carrying PfKelch13 (K13) mutations, all of whom have been found to have persistent parasitaemia by microscopy on Day 3 after treatment. Results Several studies including the multi-centre Tracking Resistance to Artemisinin Collaboration study investigated artemisinin resistance in Southeast Asia and beyond and demonstrated increasing prevalence of P. falciparum infections with slow parasite clearance rates in the Greater Mekong Subregion (GMS). K13 mutations were strongly associated with delayed P. falciparum parasite clearance, and the prevalence of the mutation PfKelch13 C580Y is increasing in the GMS. Resistance to ACT regimens is now well established in western Cambodia and in eastern Thailand, southern Laos and southern Vietnam. Moreover, the prevalence of slow P. falciparum parasite clearance has continuously increased over the past 10-15years at the Thailand-Myanmar border, in nearly all regions of Myanmar, and at the Myanmar-China border. Conclusion Multidrug resistant malaria is a rapidly increasing problem, but fortunately still limited to Southeast Asia, in particular to the GMS. In the long-term it may threaten global progress in malaria control but is not yet of concern with regards to malaria prophylaxis, as ACTs are not used for prevention in travellers, current ACT regimens are still effective in most malaria endemic areas outside the GMS and the preferred travellers' prophylaxis atovaquone-proguanil and doxycycline remain protective. However, artemsinin resistance in the GMS is of real concern to travellers as it will affect the choice of malaria treatment including standby-emergence treatment.
Gesehen am 04.11.2019
Production in progress